Spatial Analysis to Identify Hotspot of Diarrhea Among Children under Five Years in 154 Districts/Cities in Sumatera Island - Muhammad Syukri; Rd. Halim (GLOBAL HEALTH SCIENCE GROUP, 2023)
Diarrhea in under-five children is still a big challenge at the global and local level. Diarrheal disease is the second leading cause of death in children under the age of five worldwide. A spatial analysis of the incidence of diarrhea in under-five children has been conducted in Indonesia. However, there has been no research on the pattern of spatial distribution and hotspots of diarrhea in under-five children conducted on the island of Sumatra. This study aimed to identify hotspots for cases of diarrhea in under-five children on the island of Sumatra in 2018. This study used Basic Health Research data from 2018. Data analysis was carried out using Global Moran's Index and Local Indicator for Spatial Autocorrelation (LISA) ) methods. Distribution map was carried out using QGIS 3.30 software and spatial autocorrelation analysis using software open-source GeoDa 1.20 software. The results of this study found hotspots in the eastern part of the island of Sumatra, namely the Provinces of Nangroe Aceh Darussalam, North Sumatra, and Riau and low spots in the western part of the island of Sumatra, such as the Provinces of Lampung, Bangka Belitung, Riau Islands. This study suggests the health authorities to intensify programs in hotspot categories with high prevalence.